Stabilisation of multi‐loop amplifiers using circuit‐based two‐port models stability analysis - Abbas Pasdar; Masoud Meghdadi; Ali Medi (IET Circuits, Devices and Systems)
Abstract This article applies a systematic approach based on the normalized determinant function (NDF) theory to analyse stability in multi‐loop circuits and to design the required stabilization network. Presenting several provisions, the return ratios are extracted by employing immittance or hybrid matrices (Z, Y, G or H) of active two ports. Using these matrices, instead of the S‐parameters, facilitates the selection of an appropriate stabilizer network. As a practical case, a non‐uniform distributed amplifier (NDA) is designed and inspected for potential instabilities. The presented procedure detects instability associated with one of the NDA circuit's loops, and an appropriate stabilization circuit is accordingly devised. In order to validate the procedure, the designed NDA is implemented in a 0.1‐μm GaAs pHEMT process. As predicted, the measurements show oscillations, once the on‐chip stabilization circuit is disabled.